2014
DOI: 10.1007/s13224-014-0508-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Utility of Human Papilloma Virus Genotyping in Patients with Cervical Lesions

Abstract: Our study generates data of HPV prevalence in patients with cervical lesions visiting tertiary care institute. The data generated will be useful for laying guidelines for mass screening of HPV detection, treatment, and prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
6
2
Order By: Relevance
“…Type 16 was frequently the most common type encountered among the expatriates from Philippines, Arab, Indian subcontinent, and USA/Canada. [31][32][33][34][35] Among African patients, type 16 was not the commonest in present study unlike the previously available data, [36][37][38][39] commonest being type 51 in 3 patients, type 18 was not found and a few other types, 51 and 66, were noted. There was detection of a few Oncogenic HPV types which were not identified in the studies carried out in home country, [23][24][25][26] as highlighted in red in Table VIII, notably types 66,31,59,68 and 56 among Fili-pino expatriates.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…Type 16 was frequently the most common type encountered among the expatriates from Philippines, Arab, Indian subcontinent, and USA/Canada. [31][32][33][34][35] Among African patients, type 16 was not the commonest in present study unlike the previously available data, [36][37][38][39] commonest being type 51 in 3 patients, type 18 was not found and a few other types, 51 and 66, were noted. There was detection of a few Oncogenic HPV types which were not identified in the studies carried out in home country, [23][24][25][26] as highlighted in red in Table VIII, notably types 66,31,59,68 and 56 among Fili-pino expatriates.…”
Section: Resultscontrasting
confidence: 79%
“…20,[27][28][29][30] Among patients from Indian subcontinent, apart from 16 being commonest type, 66 and 35 which were not seen in previous studies, were observed. [31][32][33][34][35] Among African patients, type 16 was not the commonest in present study unlike the previously available data, [36][37][38][39] commonest being type 51 in 3 patients, type 18 was not found and a few other types, 51 and 66, were noted. Among patients of European origin, again type 16 was less common, 51 being the commonest, type 66 was seen unlike previous studies.…”
Section: Resultscontrasting
confidence: 79%
“…In part, this arises from the fact that they are constantly being exposed to a large number of risk factors facilitating the spread of sexually transmitted diseases [30]. Previous studies among the general population have reported that the prevalence of HPV ranged from 9% to 13% in the world [94]. As expected, our ndings indicated that the number of HPV-positive cases is signi cantly higher among FSWs compared to the general population, and the prevalence varied from 13% to 82% across the world.…”
Section: Discussionmentioning
confidence: 99%
“…In part, this arises from the fact that they are constantly being exposed to a large number of risk factors facilitating the spread of sexually transmitted diseases [83]. Previous studies among the general population have reported that the prevalence of HPV ranged from 9-13% in the world [84]. As expected, our findings indicated that the number of HPV-positive cases are significantly higher among FSWs compared to the general population, and the prevalence varied from 13-82% across the world.…”
Section: Discussionmentioning
confidence: 99%